The Development of Arduino Based Motorcycle Anti-theft SMS notification With GPS and Biometric Locking Alarm System: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
To combat the issue of motorcycle theft in metropolitan areas, researchers have developed aprototype anti-theft device that incorporates biometric locking, vibration detection, SMS, andGPS modules. Using an Arduino Uno microcontroller, the device enhances current securitysystems by detecting unauthorized movement, allowing only authorized individuals to start themotorcycle, and tracking the owner's whereabouts in real time. This approach aims to reducetheft and increase recovery opportunities.The prototype is developed using the device's source code, data analysis, and schematicdrawings. The biometric locking system ensures that only authorized users can start themotorcycle. The motorcycle will only start when the user's registered finger is placed on thefingerprint sensor. The researcher can add the primary fingerprint, and the user can addanother afterward. If the vibration sensor detects any illicit movement, this device will producea buzzing sound to inform anyone around. The GPS and SMS modules offer real-time locationmonitoring and theft notification by transmitting GPS to the registered number. However, thedevice cannot send SMS with GPS position where the network satellites are not accessible.The device consumes 3.9478 Ah of power when all components are functional, which isadequate for a standard motorbike battery.This study is about the innovation of an anti-theft system for motorcycles based on Arduinotechnology, which addresses the limitations of existing systems and enhances the security ofthe motorcycle. The system has several features, such as biometric-based security, an alarm,SMS, and GPS, and is an upgrade over the previous model that used RF remote. Itincorporates biometrics and alarm systems, along with SMS and GPS locator, to preventmotorcycle theft, making it more effective and convenient than the previous prototype,according to feedback from respondents.Keywords:
Keywords: Computer Science; Engineering